Cardiac fibroblasts display endurance to ischemia, high ROS control and elevated respiration regulated by the JAK2/STAT pathway. (28th November 2021) - Beà, Aida; Valero, Juan García; Irazoki, Andrea; Lana, Carlos; López‐Lluch, Guillermo; Portero‐Otín, Manuel; Pérez‐Galán, Patricia; Inserte, Javier; Ruiz‐Meana, Marisol; Zorzano, Antonio; Llovera, Marta; Sanchis, Daniel
Abstract : Cardiovascular diseases are the leading cause of death globally and more than four out of five cases are due to ischemic events. Cardiac fibroblasts (CF) contribute to normal heart development and function, and produce the post‐ischemic scar. Here, we characterize the biochemical and functional aspects related to CF endurance to ischemia‐like conditions. Expression data mining showed that cultured human CF (HCF) express more BCL2 than pulmonary and dermal fibroblasts. In addition, gene set enrichment analysis showed overrepresentation of genes involved in the response to hypoxia and oxidative stress, respiration and Janus kinase (JAK)/Signal transducer and Activator of Transcription (STAT) signaling pathways in HCF. BCL2 sustained survival and proliferation of cultured rat CF, which also had higher respiration capacity and reactive oxygen species (ROS) production than pulmonary and dermal fibroblasts. This was associated with higher expression of the electron transport chain (ETC) and antioxidant enzymes. CF had high phosphorylation of JAK2 and its effectors STAT3 and STAT5, and their inhibition reduced viability and respiration, impaired ROS control and reduced the expression of BCL2, ETC complexes and antioxidant enzymes. Together, our results identify molecular and biochemical mechanisms conferring survival advantage to experimental ischemia in CF and show their control by the JAK2/STAT signaling pathway. The presented data point to potential targets for the regulation of cardiac fibrosis and also open the possibility of a general mechanism by which somatic cells required to acutely respond to ischemia are constitutively adapted to survive it. Abstract : Cardiovascular disease is a leading cause of death worldwide. Cardiac fibroblasts play a key role in remodeling of the extracellular matrix after ischemic damage and must endure low availability of oxygen, nutrients and trophic factors in order to secrete a fibrotic scar after myocardial ischemia. Using in vitro models, Daniel Sanchez and co‐authors show that, compared to pulmonary and dermal fibroblasts, cardiac fibroblasts display high oxygen consumption capacity, high production of reactive oxygen species (ROS), improved ROS control and an overall survival advantage in ischemia‐like conditions. These attributes are governed by high constitutive activation of the JAK2/STAT pathway.